Recommendations for Thrombopropylaxis in Obstetrics and GynaecologyA SASOG Guideline - Elise Schapkaitz (South African Medical Association, 2018)
BackgroundVenous thrombo-embolism (VTE) is associated with considerable morbidity, mortality in the absence of thromboprophylaxis.MethodThe Southern African Society of Thrombosis and Haemostasis reviewed the available literature and comprehensive evidence-based guidelines on the prevention of VTE in obstetrics and gynaecology. A draft document was produced and revised by consensus agreement. The recommendations were adjudicated by an independent international expert to avoid local bias.Results and conclusionWe present concise, practical thromboprophylaxis guidelines for the clinical management of patients in obstetrics and gynaecology. Recommendations reflect current best practice, which it is hoped will lead to improved anticoagulation practice in this group of patients.